The Interactive Effect between Fermentation with Trichoderma reesei on Ammoniation on Fiber Component of Sugar Palm Pulp - Febrianti, Nurul Husnah; Subrata, Agung; Achmadi, Joelal (Bulletin of Applied Animal Research, 2020)
The purpose of this research was to examine the combination effect of fermentation time byÂ Trichoderma reeseiÂ and ammoniation on fiberÂ component ofÂ sugar palm pulp. The research used sugar palm pulp from Boyolali whichÂ was sun-dried. Sugar palm pulp fermentation withÂ Trichoderma reeseiÂ requires nitrogen for microbial growth.Â Ammoniation process couldÂ looseÂ lignocellulosic bonds and providesÂ theÂ nitrogen supply forÂ Trichoderma reesei, thereforeÂ these treatmentsÂ couldÂ optimizeÂ Trichoderma reeseiÂ in the fermentation process. SamplesÂ wereÂ fermentedÂ forÂ 0, 3 and 6 days with 1,5%Â Trichoderma reesei.Â The researchÂ treatments were allocated according toÂ a completely randomize designÂ with Â pattern of 2x3Â factorial. First factor was ammoniation treatment and second factor was variation of fermentation time. The parametersÂ observeddÂ were NDF, ADF, hemicellulose, cellulose and lignin. Research result showedÂ thatÂ thereÂ isÂ wasÂ noÂ interactive effectÂ between treatmentsÂ on reducing levels ofÂ NDF and ADF,Â butÂ interaction treatmentsÂ decreasedÂ (P<0.05)Â levelsÂ of, cellulose and lignin.Â In conclusion, the interactive effet betweenÂ fermentation time withÂ Trichoderma reeseiÂ andÂ ammoniationÂ reduce levelsÂ ofÂ hemicellulose, cellulose and ligninÂ inÂ sugar palm pulp.